Legal Protection for Consumers in the Context of Dark Patterns in Indonesian Marketplace Applications: A Comparative Study With the Netherlands - Annisa Annisa; Sylvana Murni Deborah Hutabarat (Rechtsidee, 2026)
General Background: The rapid expansion of digital marketplaces has increased consumer exposure to manipulative interface design, creating new challenges for consumer autonomy, fairness, and legal protection. Specific Background: In Indonesian marketplace applications, dark patterns appear through false urgency, hidden costs, sneak into basket, fake reviews, fake discounts, and disguised advertisements, which may harm consumers psychologically and financially. Knowledge Gap: Indonesia’s current legal framework remains general, fragmented, and reactive, while no specific regulation explicitly defines or prohibits manipulative interface design in marketplace ecosystems. Aims: This normative legal study examined consumer protection against dark patterns in Indonesia and compared it with Dutch regulations through statutory, conceptual, and comparative approaches. Results: Indonesian law only partially addresses dark patterns through consumer protection, electronic information, personal data, and electronic commerce provisions. By contrast, the Netherlands applies multi-layered protection through the DSA, WHC, GDPR-related standards, ACM technical guidelines, and proactive monitoring, including automated screening tools. Novelty: This study specifically compares Indonesia and the Netherlands in regulating and enforcing consumer protection against marketplace dark patterns. Implications: Indonesia needs explicit dark pattern regulation, operational technical guidelines, technology-based monitoring, stronger supervisory institutions, and targeted digital literacy programs to protect consumers from manipulative marketplace interfaces. Highlights: Marketplace users face psychological and financial harm. The national framework remains general and complaint based. ACM guidance demonstrates proactive technical supervision and automated screening. Keywords:  Dark Patterns, Consumer Protection, Marketplace Applications, Regulation